2007
DOI: 10.1007/s15010-007-7123-7
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcal-associated Lower Respiratory Tract Infections: A Case Report and Literature Review

Abstract: We report a rare case of bacteremic enterococcal pneumonia in an 81-year-old man, with an indolent disease course. We reviewed the literature concerning lower respiratory tract infections associated with enterococci for the burden, the pathogenesis and the clinical characteristics of these unusual infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
2
24
0
2
Order By: Relevance
“…In a study by Berk & Verghese [33] reported some Gram-positive cocci including enterococci have significance in nosocomial respiratory infection and there are chances of occurrence of enterococcal pneumonia in patients receiving broad-spectrum antibiotics [34,35]. In the present study, there is more isolation of enterococci both E. faecalis and E. faecium , from the patients of pneumonia.…”
Section: Discussionsupporting
confidence: 46%
“…In a study by Berk & Verghese [33] reported some Gram-positive cocci including enterococci have significance in nosocomial respiratory infection and there are chances of occurrence of enterococcal pneumonia in patients receiving broad-spectrum antibiotics [34,35]. In the present study, there is more isolation of enterococci both E. faecalis and E. faecium , from the patients of pneumonia.…”
Section: Discussionsupporting
confidence: 46%
“…We conducted a literature search based on PubMed in an attempt to identify all published cases of pleuropulmonary infection due to enterococcus, without time limits. Twenty-four cases of Enterococcus-associated pleuropulmonary infection previously published in the literature were eventually summarized in Table 1 [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The enterococcal pneumonia cases previously described in the literature mainly occurred in elderly patients with immunosuppression, organ transplantation, hematological malignancies, solid cancer, renal failure, cardiocerebrovascular disease and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia caused by enterococci has not been previously reported from Iran. Respiratory tract infections caused by enterococci are exceedingly rare [19]. The oropharynx has been identified as a colonization route of enterococci in the respiratory tract [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory tract infections caused by enterococci are exceedingly rare [19]. The oropharynx has been identified as a colonization route of enterococci in the respiratory tract [19,20]. Gastric colonization of enerococci has been also suggested as a reservoir of enterococci involved in nosocomial infections [20].…”
Section: Discussionmentioning
confidence: 99%